The investigation of relationship between sleeping disorder and academic achievement among Faculty of Education students at UiTM / Muhammad Syafiq Samsuri - Samsuri, Muhammad Syafiq (Faculty of Education, 2014)
This research is a investigation of sleep disorder and academic achievement among students Faculty of Education UiTM Shah Alam. Two hundred and ten respondents were randomly chosen based on their course which 30 students in each course. The collected data were analyzed using the software Statistical Package for Social Science (SPSS). Frequency and percentages were used to analyze the current (GPA) of students. Frequency, percentages, mean and standard deviation were used to examine the type of sleep disorder among the students and Pearson Correlation Coefficient was used to analysis the data on relationship between sleep disorder and academic achievements (GPA). Results showed that sleep disorder and academic achievement is related. So, there is a relationship between sleep disorder and academic achievement in the faculty of Education UiTM Shah Alam. This means the type of sleep disorder such as insomnia, parasomnia, sleep apnea and sleep inadequate hygiene and affects academic achievements of the students. The researcher recommended that students need consider the amount of sleep, feelings before sleep, type and amount of food and beverage taking before sleep to maintain and improve daily productivity.